Graphene-Based Electrochemical Sensors for Heavy Metal Ions Detection: A Comprehensive Review - Dilshad, Muhammad; Hussain, Tariq; Ali, Shahbaz; Shahzad, Muhammad Shakeel; Javed, Muhammad; Ahmad, Farhan Nazir; Zaki, Asaad Ahmad (Bumi Publikasi Nusantara, 2025)
The accumulation of heavy metallic ions in the human body causes serious damage. The tracking and removal of these ions is very necessary and that is done via electrochemical sensors because of quick response, high sensitivity, and low but large detection range. In this regard, the surface of the electrode plays a critical role in electrochemical performance. Here, we present a detailed review of work that has been done in the past to modify the surface of electrodes by testing the carbon nanoparticles i.e. graphene or graphene derivatives, and their combination with other nanoparticles. Mixing graphene or graphene oxide with other organic or inorganic materials forms nanocomposites which help to detect various kinds of heavy metal ions such as cadmium, mercury, copper, lead, zinc, etc. in tap water or food items. This review article includes the synthesis methodologies, working mechanisms, advantages, disadvantages, and future prospectus of this field.